2010
DOI: 10.1063/1.3506533
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization reversal dynamics, nucleation, pinning, and domain wall propagation in perpendicularly magnetized ultrathin cobalt films: Influence of the Co deposition rate

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…The magnetic domain density increase is explained by an increase in the density of defects associated with nucleation centers. [41] Defects can also be places of weak anisotropy caused by the thermal effects.…”
Section: Magnetization Reversal Dynamicsmentioning
confidence: 99%
“…The magnetic domain density increase is explained by an increase in the density of defects associated with nucleation centers. [41] Defects can also be places of weak anisotropy caused by the thermal effects.…”
Section: Magnetization Reversal Dynamicsmentioning
confidence: 99%
“…Recent experiments showed that magnetic nanoparticles possess either Gaussian distributions f G [3,10,14] or log-normal distributions f LN of sizes [1,11,12]. For small variances, log-normal distributions look similar to Gaussian distributions.…”
Section: B Distributions Of Magnetic Anisotropy Dmentioning
confidence: 99%
“…Recent advances in nanotechnology have allowed synthesis of nanoscale magnetic particles or molecules in various forms, such as in solutions, adsorbed at surfaces, or as powder compacts [1][2][3]. This was motivated by their applications for magnetic storage media [4,5], biosensors [6], and contrast agents in magnetic resonance imaging [7][8][9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They also have various applications including information storage devices [1,2], sensors, and contrast agents in magnetic resonance imaging [3][4][5]. Synthesized magnetic nanoparticles have typically large distributions of size and shape which influence their equilibrium and nonequilibrium properties [6][7][8][9][10][11][12][13]. For example, the size and shape distributions induce distributions in the magnetic anisotropy barrier, magnetization switching or relaxation, and blocking temperature.…”
Section: Introductionmentioning
confidence: 99%